SCIENTIFICALLY GROUNDED CONCEPTIONS, THEORIES AND SCHOOL PRINCIPALS PROFESSIONAL DEVELOPMENT VARIATIVE MODULES - Arhipova, Olga; Kokina, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
At present, there is an objectively determined process of the formation of a new type of education paradigm that envisages both in content and in organization passage from an informational-reproductive model to that of creative search. Solution of these problems requires operative organization in Latvia of the growth of professional competence of education institution principals as managers in the sphere of education. Investigation of the professional development of education institution principals sets as imperative the philosophical approach of constructivism and the communicative approach. Both conceptual approaches make it possible to elaborate a scientific conception that includes several variative modules that secure a multi-dimensional view of the professional development of education institution principals.Professional competence of education institution principals is a complex notion with manifold content. It comprises a dynamic combination of knowledge and personality traits for the implementation of education institution principals’ professional development. The content of the variative module system and its sub-modules is tended to competence improvement in a particular sphere of education. Its aim is providing an opportunity of improving education institution principals’ professional aptitude by acquiring new developments in the content and methods of education for their creative application in the process of education management in line with aims, learners’ needs and interests, management philosophy, and basic principles of management.